Participation of LPMD in Village Infrastructure Development - Sulistiyono; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
The general background infrastructure development is fundamental for enhancing the quality of life and economic prospects in rural communities. Specific background in Indonesia, institutions such as Lembaga Pemberdayaan Masyarakat Desa (LPMD) are pivotal in facilitating this process. Knowledge gap despite their critical role, there is a scarcity of research addressing the specific contributions of LPMD to infrastructure projects at the village level. Aims This study aims to bridge this knowledge gap by investigating the involvement of LPMD in the planning, implementation, and supervision of infrastructure development within a village context. The Results Utilizing a descriptive qualitative approach, the results indicate that LPMD actively engages in project implementation, proposes community-based programs, and oversees project execution to ensure accountability and transparency. Novelty This research contributes novel insights into the diverse roles played by LPMD, showcasing both active and passive participation in infrastructure initiatives. The implications highlight the necessity for local governments to recognize and strengthen the involvement of LPMD in development processes, ensuring that community perspectives are effectively integrated into planning and execution, which may lead to more sustainable and impactful infrastructure development in rural settings. Highlights: LPMD plays a crucial role in infrastructure planning and implementation. The study highlights both active and passive participation of LPMD. Community involvement is essential for sustainable development outcomes. Keywords: Infrastructure Development, LPMD, Community Empowerment, Village Participation, Sustainable Development